Management of Locally Advanced Basal Cell Carcinoma with Sonic Hedgehog Pathway Targeted Therapy: A Case Report and Discussion - Neal Ferrin; Darwin Edmond; Ryan Jones; Laurence E. McCahill (Karger Publishers, 2024)
Introduction: Basal cell carcinoma (BCC) is the most common skin malignancy in the world. While most lesions are treated using surgical methods, others may present as locally advanced or metastatic disease and are not amenable to surgical therapy alone. Treatment with sonic hedgehog pathway inhibitors (vismodegib, sonidegib) is designed to inhibit key signaling proteins and gene pathways involved with BCC to reduce the uncontrolled proliferation of basal cells in complicated disease and can be invaluable in treating patients with advanced disease. Case Presentation: We describe the course of a 68-year-old man who presented with a 7.2 × 6 cm exophytic and ulcerated locally invasive BCC of his upper back. The patient was started on daily vismodegib treatment with the goal of eventual surgical resection. After 11 weeks of therapy, he had significant improvement in both wound size and appearance. After 18 weeks of therapy, he had achieved a near complete clinical response of the central aspect of lesion with three remaining small peripheral lesions. These lesions were biopsied, and two were found to be negative for malignancy, while a small inferior nodule was positive for squamous cell carcinoma (SCC). Vismodegib therapy was discontinued after a total of 26 weeks of therapy. Excision of the SCC was performed, and the patient remains disease free at 2 years. Conclusion: This case report shows the efficacy of hedgehog pathway inhibitor therapy in the treatment of a locally advanced BCC with complete pathologic response, not requiring surgical intervention.